Kepemimpinan Transformasional Kelompok Kerja Guru (KKG) Pendidikan Agama Islam (PAI) Sekolah Dasar di Kecamatan Ciracas Jakarta Timur - Tri Hidayanti; Faqih Purnomosidi; Anniez Rachmawati Musslifah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Teachers are a primary factor in determining the quality of education. The high qualifications, competence, and dedication of teachers will produce students who are academically, skillfully, emotionally, morally, and spiritually mature. PAI is a conscious and planned effort to prepare students to know, understand, appreciate, believe, be devout, and have noble morals in practicing Islamic religious teachings with the primary sources of Al-Qur’an and Hadith. Through KKG, teachers have the opportunity and potential to discuss solving problems in class.Transformational leadership is a way in which leaders strengthen attitudes of mutual cooperation and believe in collective self-improvement and team learning. The research aims to find out how transformational leadership is possessed by the PAI SD KKG at Ciracas district in East Jakarta. The qualitative research method used was observation, interviews, and documentation with five KKG members, namely deputy chairman, secretary, treasurer I, treasurer II, coordinator for creativity and arts as the primary informant and two members as supporting informants.The research concluded that transformational leadership in the PAI SD KKG at Ciracas district in East Jakarta is excellent because the members are very satisfied with the chairman's leadership.